Reglas de responsabilidad: Una taxonomía económica - Dari-Mattiacci, Giuseppe (2015)
The analysis of tort law is one of the most well-developed applications of economic methodology in the study of law. in this essay, we provide an overview of the economic approach to tort law, analyzing the effects of liability rules on care incentives. We catalogue a variety of possible tort regimes, systematically breaking down possible assignments of liability in terms of primary and secondary rules, and describe how their permutations distribute the costs of accidents (and the concomitant incentives to exercise precautionary care). We further consider what factual circumstances may render one tort regime preferable to another from the perspective of policymakers.